Potential For The Development Of The Promotion Sarongge Tea In The Application Of The Green Tourism Value In Saronnge Village, Pacet Jawa Barat - Ananditya Savitri Novi Utami (Jurnal Hospitality dan Pariwisata, 2018)
ABSTRACT Tourism is now able to be a leading sector in Indonesia. Government tourism programme along get through with the 4.0 industry. A billion state money already implementing to develop tourism village which it will be reform the welfare of the village human life quality. This phenomenon the tourism diversity especially referring to tourism village always become potential income through natural attraction and culture. Tourism village in Sarongge is one of the about 200 and more that serve village which become edutourism. Village of Sarongge which located in Cianjur West Java. Sarongge village is one of the result of the participation of the community based who it focused with its product in edutourism. The development of edutourism in value in green area has managed to create and has become priorities economic growth for the local people of Sarongge village.This paper will highlight the issues that promotion edutourism in application of value green concept in Sarongge which have product strength in tea and coffee plantation, also many more tourism activities is an effort to develop edutourism concept through tea and coffee plantation. The result of this paper find that promotion still get adversity to create and promote for tea and coffee plantation as a core from edutourism in Sarongge village. Keywords: Edutourism, Sarongge Tea, Green Tourism